Mutu awal benih cabai rawit hiyung berdasarkan tingkat kemasakan dan metode ekstraksi - Muhammad Syamsudin Atuf; Baktinur Ismuhajaroh; Gani Jawak (Jurusan Agroteknologi, 2025)
The ripening stage of chili fruits constitutes a critical factor affecting seed quality. This study was conducted to evaluate the effects of fruit ripening stage and extraction method on the initial quality of Hiyung chili seeds. The experiment was arranged in a completely randomized design with two factors: ripening stage (W) and extraction method (E). The ripening stage factor comprised four levels: green (W1, Strong Yellow Green 143A), brown (W2, Light Olive 152A), orange (W3, Vivid Reddish Orange N30A), and red (W4, Vivid Red 44A), as determined using the RHS Color Chart. The extraction methods included manual (E1) and blender extraction (E2). In total, eight treatment combinations were evaluated, each replicated four times, resulting in 32 experimental units. Seed quality was assessed using the paper germination test with 50 seeds per replicate. The parameters measured included initial moisture content (MC), germination percentage (GP), growth rate (GR), vigor index (VI), germination uniformity (GU), and seed electrical conductivity (EC). The MC across all treatments ranged from 74% to 85%. Seeds from the red maturity stage (W4) exhibited the highest GP and GU, recorded at 24% and 6.75%, respectively. The highest GR was observed in the orange maturity stage (W3) treatment (1.92%). All treatments yielded a vigor index of 0%. The combination of red maturity stage with manual extraction (W4E1) resulted in the highest GP, GU, and GR values of 33%, 10%, and 2.67%, respectively. The ripening stage significantly influenced seed quality parameters, specifically GP, GU, and GR. The extraction method had no significant effect on these parameters. However, the interaction between ripening stage and extraction method significantly affected GP and GU.